(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The impact of technologies on humans life has completely took a place in every forms of words as it is in traveling, in learning or in communication from others and these gadgets has made our life easy. The technology also help to improve the standards of communications, educations, health-care and many more. Therefore, many companies have already shifted to the new technologies and some are planning to move from offline services to online services. This paper explains that, these technologies have made our life easy and is now became important in every field. Before the arrival of technologies, everyone gets difficulties in communicating and sharing their data or views. The growth of internet has increased because all the facilities are available on every platforms and every one can excess that easily from everywhere. However, on other side these are affecting the children because of the misuse of the internet. So these new technologies have the bad impacts as well as good impacts on their convince to use the new technologies. Earlier there is no use of online shopping everyone goes and buy it traditionally but now mostly everyone buys it online as per their convince. In future, the technologies will get vaster from now and have many scopes to achieve the higher growth.